2001
DOI: 10.4049/jimmunol.167.8.4180
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NKT Cells by Ly49: Analysis of Primary NKT Cells and Generation of NKT Cell Line

Abstract: TCRαβ+NK1.1+ (NKT) cells are known to express various NK cell-associated molecules including the Ly49 family of receptors for MHC class I, but its functional significance has been unclear. Here, we examined the expression of Ly49A, C/I and G2 on various NKT cell populations from normal and MHC class I-deficient C57BL/6 mice as well as their responsiveness to α-galactosylceramide (α-GalCer), a potent stimulator of CD1d-restricted NKT cells. The frequency and the level of Ly49 expression varied among NKT cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 41 publications
0
57
2
Order By: Relevance
“…The role for differential expression of Ly49 molecules on NKT cell subsets is unclear. Maeda et al (64), have shown that Ly49 molecules can suppress NKT cell activation and IFN-␥ production in response to ␣-GalCer, but they did not distinguish between different Ly49 molecules. Ly49G2 recognizes the H-2 d haplotype of MHC class I, which is absent in C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…The role for differential expression of Ly49 molecules on NKT cell subsets is unclear. Maeda et al (64), have shown that Ly49 molecules can suppress NKT cell activation and IFN-␥ production in response to ␣-GalCer, but they did not distinguish between different Ly49 molecules. Ly49G2 recognizes the H-2 d haplotype of MHC class I, which is absent in C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although all Ly49 receptors were cloned from NK cells, expression of Ly49 is not restricted to NK cells but it is also detected in CD8 ϩ T (32) and NKT cells (33). It has been reported that Ly49-negative NKT cells can be stimulated with ␣-GalCer-pulsed DCs, whereas Ly49-positive NKT cells do not respond (34). Thus, we examined the expression of Ly49A, Ly49C/I, and Ly49G2 on NKT cells from LFA-1 ϩ/ϩ and LFA-1…”
Section: Activation Of Nkt Cells In Lfa-1 ϫ/ϫ Micementioning
confidence: 99%
“…Next we asked whether the deficiency of Bhlhe40 might affect the maturation status of iNKT cells. To answer this question, thymic iNKT cells from WT or Bhlhe40 −/− mice were used to compare the expression of Ly49 family members, which are described as being expressed on both developing and mature iNKT cells (15). Again, no major differences were observed in the expression of Ly49 family members between WT and Bhlhe40 −/− iNKT cells (Fig.…”
Section: Bhlhe40mentioning
confidence: 99%